ALTERNATIVE UNBabc MAPPING FUNCTION FOR TROPOSPHERIC DELAY - Sakidin, Hamzah; Tay, Choo Chuan (2010)
The UNBabc(E) mapping function models should be simplified to allow faster calculation and also better understanding of the models. Many modern mapping function models use mapping functions in the form of continued fractions which is quite tedious in calculation. There are 11 mathematical operations for UNBabc(E)lo be carried out before getting the mapping function scale factor. The mapping functions for UNBabc(E) models for hydrostatic component is given in a form of continued fraction are to be simplified, due lo its ability to calculate mapping function value down to 2 degree of elevation angle. By using linear, hyperbolic, logarithm and also regression- method, the mapping function models can be simplified and at the same time can produce the same result. This model can be suggested to be an alternative to the established mapping function.